Three-dimensional transesophageal echocardiography in the guide of cardiac mass biopsy: future prospectives. Issue 1 (January 2018) - Di Lisi, Daniela; Raspante, Donatella; Lavanco, Vincenzo; Curzi, Mirko; Macaione, Francesca; Cavallaro, Massimo; Tona, Riccardo; Novo, Giuseppina; Novo, Salvatore; Bragato, Renato M.
Abstract : Supplemental Digital Content is available in the text